Duplex surface treatment of stainless steel X12CrNi 18 8 - Kadlec, J.; Dvorak, M. (Проблемы прочности, 2008)
Described technology of stainless steel duplex surface treatment is based on the plasma nitriding of the component in micropulse plasma and subsequent coating by Ni and composite Ni/diamond film. The formed duplex coating is characterized by very good mechanical properties, e.g., an excellent abrasion resistance, a low friction coefficient and a high hardness. Описана технология двухфазной поверхностной обработки нержавеющей стали, которая базируется на плазменном азотировании детали микроимпульсной плазмой с по следующим нанесением никелевого покрытия и композитной никель-алмазной пленки. Полученное двухфазное покрытие характеризуется очень высокими механическими свойствами, т.е. повышенной износостойкостью, низким коэффициентом трения и высокой твердостью.